L’espace d’habitation comme miroir identitaire. Le cas des migrants de Patamban (Michoacán, Mexique) aux États-Unis - Frida Calderón Bony (Cahiers des Amériques Latines)
In this article we put into consideration the relationship that migrants use to build their living spaces. We start from the hypothesis that there is a relationship between the subject and its habitat that arises precisely from its experience in mobility and, from the case of the migrants from Patamban (Michoacán, Mexico) we take interest in the habitation practices in order to propose an interpretation on the form of such relationship. Our analysis leads to a process that defines the identity of the migrant, starting from their homes (one in the country of origin, the other in the country of destination) in which the habitat works as a spatial resource for the benefit of the definition of the subject. Starting from the concept of "spatial unfolding ", we show that the habitat works both as a form of self‑expression and as a reaffirmation territory of identity for the mobile subject.